2016
DOI: 10.1038/scsandc.2015.25
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of training with the ReWalk exoskeleton on quality of life in incomplete spinal cord injury: a single case study

Abstract: It is a single case study. An investigation to what extent the quality of life (QoL) of patients with spinal cord injury can be influenced by the training with an exoskeleton. The study was carried out at a Hospital for neurological rehabilitation, Germany. One patient (male, 22 years), initially unable to walk independently after traumatic spinal cord injury with neurological level Th11 (ASIA Impairment Scale C) was recruited for this study 1 year after injury. The progress of the first 6 months of ReWalk tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Similar values on QoL were found in our study. Improvements in QoL have previous also been reported in case studies using the exoskeletons ReWalk (ReWalk Robotics Ltd, Yokneam, Israel (39) and HAL (32).…”
Section: Quality Of Lifementioning
confidence: 56%
“…Similar values on QoL were found in our study. Improvements in QoL have previous also been reported in case studies using the exoskeletons ReWalk (ReWalk Robotics Ltd, Yokneam, Israel (39) and HAL (32).…”
Section: Quality Of Lifementioning
confidence: 56%
“…Moreover, in a 2-case report by Cruciger et al [30], both subjects (10 and 19 years; AIS A) reported increased health-related quality of life scores for all 8 domains of the Short Form Health Survey (SF-36). Similarly, a case study involving 1 individual with paraplegia (1 year; AIS C) who was not independently ambulatory reported increased scores in 6 out of 8 areas of the SF-36 (physical functioning, physical role function, physical pain, general health, vitality, physical well-being) following 6 months of rehabilitation with the ReWalk powered exoskeleton [38]. Overall, the use of powered exoskeletons, both to stand upright and to walk, has consistently been shown to improve health-related quality of life measures in these few small studies.…”
Section: Quality Of Lifementioning
confidence: 94%
“…We present in 1 place a collection of the purported benefits using rigid, powered exoskeletons of the lower extremity with scope narrowed to the systems available in the USA between 2010 and 2018 that facilitate ambulation in individuals with both complete and incomplete SCI without body weight support. The benefits addressed include strengthening impaired muscles, improving walking speed and efficiency, and addressing secondary medical conditions following SCI such as spasticity [27][28][29], pain [28,30,31], changes in the cardiovascular system and metabolism [32][33][34][35][36], bowel [27,35,37], bone [34], and overall quality of life [28,30,38].…”
Section: Lower Extremity Roboticsmentioning
confidence: 99%
“…In rehabilitation medicine, exoskeletons are used to restore function . For example, these devices enable assistive ambulation for spinal cord injury or multiple sclerosis patients . These devices can also be used as assistive appliances to restore function to an arm or leg, or as a therapeutic device to train an individual's muscles or nervous system to help overcome a disability .…”
Section: Introductionmentioning
confidence: 99%